STRATEGI PROMOSI PERTUNJUKAN ADAT BAGI WISATAWAN KAPAL PESIAR DI PELABUHAN GILI MAS, LOMBOK - Danu Satria Prayuda; I Putu Septian Adi Prayuda; Erri Supriyadi (Kepariwisataan: Jurnal Ilmiah, 2026)
ABSTRACT The rapid growth of the global cruise tourism industry has encouraged destinations in Indonesia to strengthen ports as gateways for international tourists. Gili Mas Port in Lombok has strategic potential due to its proximity to leading tourist destinations and the richness of Sasak culture. However, tourism promotion particularly traditional performances as sustainable attractions, has not yet been managed optimally and in an integrated manner. This study aims to analyze tourism promotion strategies for cruise ship passengers at Gili Mas Port and to identify the challenges encountered. The research employed a qualitative descriptive approach using participatory observation, in-depth interviews with key stakeholders (KSOP Lembar, PT Pelindo, Tourism Office, NTB Regional Tourism Promotion Board, travel agent associations, and cruise tourists), and documentation studies. Data were analyzed using the interactive model of Miles and Huberman. The findings indicate that traditional performances are still presented mainly as ceremonial welcoming events and have not been optimally integrated into an Integrated Marketing Communication (IMC) strategy. In addition, the use of digital media remains limited. The main challenges include stakeholder coordination, limited duration of cruise tourists’ visits, and the absence of a sustainable cultural promotion model. This study recommends strengthening culture-based IMC strategies to enhance the competitiveness of cruise tourism in Lombok. Keywords: Traditional Performances; Promotion; Cruise Tourism; IMC; Gili Mas Port ABSTRAKPerkembangan industri wisata kapal pesiar global mendorong destinasi di Indonesia untuk memperkuat pelabuhan sebagai pintu masuk wisatawan mancanegara. Pelabuhan Gili Mas Lombok memiliki potensi strategis karena kedekatannya dengan destinasi unggulan dan kekayaan budaya Sasak. Namun, promosi daya tarik wisata, khususnya pertunjukan adat sebagai atraksi berkelanjutan, belum dikelola secara optimal dan terpadu. Penelitian ini bertujuan menganalisis strategi promosi daya tarik wisata kepada wisatawan kapal pesiar di Pelabuhan Gili Mas serta mengidentifikasi tantangan yang dihadapi. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi partisipatif, wawancara mendalam terhadap pemangku kepentingan (KSOP Lembar, PT Pelindo, Dinas Pariwisata, BPPD NTB, asosiasi travel agent, dan wisatawan kapal pesiar), serta studi dokumentasi. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa promosi pertunjukan adat masih bersifat seremonial, belum terintegrasi secara optimal dalam strategi komunikasi pemasaran terpadu (IMC), dan pemanfaatan media digital masih terbatas. Tantangan utama meliputi koordinasi antar-stakeholder, keterbatasan durasi kunjungan wisatawan kapal pesiar, serta belum adanya model promosi budaya yang berkelanjutan. Penelitian ini merekomendasikan penguatan strategi IMC berbasis budaya lokal untuk meningkatkan daya saing pariwisata kapal pesiar di Lombok. Kata Kunci : Pertunjukan Adat; Promosi; Kapal Pesiar; IMC; Pelabuhan Gili Mas